ALTERNATIVE ELECTRIC PROPULSION SYSTEM FOR HEV MANIPULATING PREDICAMENT VIA POWER PREPOTENCY - Reshma S. (Proceedings on Engineering Sciences, 2023)
Hybrid Electric Vehicle (HEV) is considered as the evolution of Electric vehicle in which hydrogen is taken as a fuel. In this paper, a novel Alternative Electric Propulsion System has been proposed to tackle the major issues in HEV such as, the long auto ignition delay, hydrogen gas fuel depletion and power energy demand. Initially, Perpetual extent cauldron has been introduced to tackle the long auto ignition delay via considering pressure levels, lean, quasi-stoichiometric and rich conditions for estimation of delay time which handled through simulation. Consequently, Canny predicament approach is adopted to handle the hydrogen depletion in emergency cases by introducing predicament manipulate algorithm where fuel reserved in house as well as boost converter will contributed in this algorithm to fulfill the hydrogen demand. In addition, Astute power prepotency is proposed to manage the power energy demand with the cooperation of manifold proxy system, which can be achieved via communication between multiple agents via supervising agent as well as predicament manipulate algorithm can subordinate for such power energy demand. Thus it provides, an efficient electric propulsion system for hybrid electric vehicle with power management. This proposed system has been implemented in MATLAB Simulink and compared with the recent researches.